Light‐Propelled Nanorobots for Facial Titanium Implants Biofilms Removal. Issue 22 (10th May 2022) - Ussia, Martina; Urso, Mario; Kment, Stepan; Fialova, Tatiana; Klima, Karel; Dolezelikova, Kristyna; Pumera, Martin
Abstract: Titanium miniplates are biocompatible materials used in modern oral and maxillofacial surgery to treat facial bone fractures. However, plate removal is often required due to implant complications. Among them, a biofilm formation on an infected miniplate is associated with severe inflammation, which frequently results in implant failure. In light of this, new strategies to control or treat oral bacterial biofilm are of high interest. Herein, the authors exploit the ability of nanorobots against multispecies bacterial biofilm grown onto facial commercial titanium miniplate implants to simulate pathogenic conditions of the oral microenvironment. The strategy is based on the use of light‐driven self‐propelled tubular black‐TiO2 /Ag nanorobots, that unlike traditional ones, exhibit an extended absorption and motion actuation from UV to the visible‐light range. The motion analysis is performed separately over UV, blue, and green light irradiation and shows different motion behaviors, including a fast rotational motion that decreases with increasing wavelengths. The biomass reduction is monitored by evaluating LIVE/DEAD fluorescent and digital microscope images of bacterial biofilm treated with the nanorobots under motion/no‐motion conditions. The current study and the obtained results can bring significant improvements for effective therapy of infected metallic miniplates by biofilm. Abstract : Light‐driven self‐propelled tubular black‐TiO2 /Ag nanorobots are used to remove multispecies biofilm from facial titanium miniplates routinely practiced in oral and maxillofacial surgery. UV to visible‐light triggers multimodal motion behaviors, including rotational and random swimming, which accelerate the biofilm eradication through the "on the fly" release of reactive oxygen species and Ag ions.